Chemical composition and egg production capacity throughout bloom development of ctenophore Mnemiopsis leidyi in the northern Adriatic Sea - Rečnik, Kevin; Klun, Katja; Lipej, Lovrenc; Malej, Alenka; Tinta, Tinkara (PeerJ, 2024)
High abundances of gelatinous zooplankton (GZ) can significantly impact marine ecosystem by acting as both sink and source of organic matter (OM) and nutrients. The decay of GZ bloom can introduce significant amount of OM to the ocean interior, with its variability influenced by GZ life traits and environmental factors, impacting microbial communities vital to marine biogeochemical cycles. The invasive ctenophores Mnemiopsis leidyi has formed massive blooms in the northern Adriatic Sea since 2016. However, the variability in the chemical composition and egg production of blooming populations, as well as the role of environmental factors in governing this variability, remains largely unknown. Our analysis of biometry, chemical composition, and fecundity of M. leidyi sampled in the Gulf of Trieste in 2021 revealed stable carbon and nitrogen content throughout bloom development, with no significant correlation with seawater temperature, salinity, oxygen, and chlorophyll a concentration. Although the studied population exhibited homogeneity in terms of biometry and chemical composition, the number of produced eggs varied substantially, showing no clear correlation with environmental variables and being somewhat lower than previously reported for the study area and other Mediterranean areas. We observed a positive correlation between the wet weight of individuals and the percentage of hatched eggs, as well as a significant positive correlation between the percentage of hatched eggs and ambient seawater temperature. Additionally, we noted that the speed of hatching decreased with decreasing seawater temperature in autumn, corresponding to the end of M. leidyi bloom.
Keywords: Ctenophore; Biogeochemistry; Egg production capacity; Invasive species; Chemical composition; Marine ecology